2019
DOI: 10.5430/ijfr.v11n1p147
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Decentralization and Economic Growth in Thailand: A Cross-Region Analysis

Abstract: Prior to the 1997 decentralization, over 90% of national revenue in Thailand were held at the central government and less than 10% of public expenditure were allocated to local governments across country. Lack of adequate revenue and access to sufficient expenditure budget has caused disparity and ineffectiveness of public services and economic development at the local level. This study examines the effects of the fiscal decentralization on the economic growth in Thailand from 2004 to 2017. The research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…It is also consistent with the empirical results of Carniti et al (2019) who find a positive relationship between decentralisation and growth (however they note that this relationship is not linear). Similarly, Canavire-Bacarreza et al (2020), Thanh and Canh (2020), Nantharath et al (2020) and Rodr ıguez-Pose and Mu stra (2022) find a positive relationship between fiscal decentralisation and economic growth.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It is also consistent with the empirical results of Carniti et al (2019) who find a positive relationship between decentralisation and growth (however they note that this relationship is not linear). Similarly, Canavire-Bacarreza et al (2020), Thanh and Canh (2020), Nantharath et al (2020) and Rodr ıguez-Pose and Mu stra (2022) find a positive relationship between fiscal decentralisation and economic growth.…”
Section: Resultsmentioning
confidence: 85%
“…Firstly, there has been a global trend towards fiscal decentralisation over the past 30 years (Canavire-Bacarreza et al, 2020). Fiscal decentralisation proponents contend that higher levels of economic growth and improved government efficiency result from greater proximity to businesses and citizens helping government decision-makers better comprehend the needs and demands of citizens (Oates, 1972;Tiebout, 1956;Giordano, 2000;Morgan, 2002;Rodr ıguez-Pose and Sandall, 2008;Canavire-Bacarreza et al, 2020;Nantharath et al, 2020;Li et al, 2021). Academics, national governments and organisations appear convinced of the economic benefits of fiscal decentralisation (Rogr ıguez-Pose and Kroijer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fiscal autonomy has a positive influence on economic growth across provinces in Vietnam (Nguyen et al, 2019). The study found empirical evidence of positive results of revenue decentralization, transfer dependency, and vertical fiscal imbalance on regional economic growth across 5 regions (Nantharath et al, 2020). The economic growth has significant effect on the social welfare (Simanjuntak et al, 2017).…”
Section: Economic Growthmentioning
confidence: 90%
“…ketergantungan transfer menggambarkan seberapa besar ketergantungan daerah terhadap dana yang ditransfer oleh pusat dalam hal pengelolaan keuangan daerah. Indikator tersebut dihitung dari rasio antara dana transfer dengan total penerimaan daerah.. Hal ini sejalan dengan penelitian (Nantharath et al, 2019) yang memiliki hasil bahwa ketergantungan transfer dari pemerintah pusat ke pemerintah daerah berpengaruh positif terhadap pertumbuhan ekonomi.…”
Section: Pendahuluanunclassified
“…Namun, hasil penelitian ini bertentangan dengan penelitian dari (Nantharath et al 2019) yang menunjukkan bahwa desentralisasi pengeluaran berpengaruh negatif terhadap pertumbuhan ekonomi. hal ini disebabkan oleh ketidakstabilan politik yang memberikan dampak signifikan pada hubungan antara pemerintah pusat dan daerah, khususnya pada redistribusi anggaran pemerintah daerah di seluruh negara.…”
Section: Pengaruh Rasio Belanja Modal Terhadap Pertumbuhan Ekonomiunclassified